The moral constituents of the Moslem society in the light of al-Hojorat sura - Yahia Dahi Ali Shatnawi (Journal of Educational Sciences, 2009)
This research aims to find out that moral constituents is the most important factor in keeping the entity of the society together strong , incapable to collapse for any weakest joggling disaster destroy its existence. while material constituents still an additional sources and support and can be an obstacle in its way of civilization. This research presents alive sample through one of the holy quran verses , al-Hojorat sura , which talks about the main moral constituents in the society, where indeedly Assahaba society roses within these constituents, they were the best example generation for human kinds have ever been , inspite of the rareness of resources and abilities .